2014
DOI: 10.1186/1756-0500-7-422
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing nutritional environments through access to fruit and vegetables in schools and homes among children and youth: a systematic review

Abstract: BackgroundLow fruit and vegetable (FV) consumption is one of the top 10 global risk factors for mortality, and is related to increased risk for cancer, cardiovascular disease and diabetes. Many environmental, sociodemographic and personal factors affect FV consumption. The purpose of this review is to examine the effects of interventions delivered in the home, school and other nutritional environments designed to increase FV availability for five to 18-year olds.MethodsThe search included: 19 electronic biblio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 39 publications
4
30
0
6
Order By: Relevance
“…Policies enacted at organizational and government levels, nearly all of which were implemented within schools, appeared similarly effective amongst disadvantaged children. Other reviews have also found a majority of child-related interventions to be conducted in schools (54,59), with one finding local school food service policies to be more effective in enhancing food environments compared with broader state/federally mandated policies targeting a wider variety of settings (54). It is clear from our results that schools can provide a supportive context for focused intervention in support of relatively highquality controlled studies.…”
Section: Authors and Yearsupporting
confidence: 58%
See 1 more Smart Citation
“…Policies enacted at organizational and government levels, nearly all of which were implemented within schools, appeared similarly effective amongst disadvantaged children. Other reviews have also found a majority of child-related interventions to be conducted in schools (54,59), with one finding local school food service policies to be more effective in enhancing food environments compared with broader state/federally mandated policies targeting a wider variety of settings (54). It is clear from our results that schools can provide a supportive context for focused intervention in support of relatively highquality controlled studies.…”
Section: Authors and Yearsupporting
confidence: 58%
“…Many reviews have examined the impact of school‐based interventions on obesity‐related outcomes in children . The current study is the first, to our knowledge, to examine the impact of school‐based policies targeting disadvantaged children.…”
Section: Discussionmentioning
confidence: 98%
“…High-income earning countries have achieved reduction in hypertension through the implementation of robust public health policies aimed at reducing salt in processed food, improving the availability and affordability of fruits and vegetables (38), and creating environments that promote physical activity. In low-and middle income countries however, shortcomings in these public health policies and others have facilitated increasing trends of hypertension (3).…”
Section: P R E V E N T I O N a N D C O N T R O L M E A S U R E Smentioning
confidence: 99%
“…FV from home gardens have been documented as an important supplemental sources of nutrients, contribute to food and nutritional security, and allow families to produce their own fruits and vegetables organically (13,15,16). Vegetable gardens introduce more variety into the diets of children (17). Consequently, the intake of various nutrients such as vitamin A and calcium is increased with gardening (14).…”
Section: Introductionmentioning
confidence: 99%